ENVIRONMENT MONITORING USING DIGITAL ELEVATION MODELS BASED ON SATELLITE DATA – A TOOL FOR SUSTAINABLE DEVELOPMENT - MUNTEANU, Laura Ionela; BODA, Florentin (Annales Universitatis Apulensis Series Oeconomica; Vol 2 No 16 (2014): Annales Universitatis Apulensis Series Oeconomica, 2014)
With the increasing number of launched satellite missions in the past years, there were developed new methods for receiving and combining satellite data, obtaining very accurate results for mapping the Earth, but also for monitoring the environment in time.  Knowing the environment and having the possibility to analyze its evolution in time represent key elements for a sustainable development. This paper presents theoretical, economic and social aspects regarding the advantages of using digital elevation models based on satellite data for monitoring the environment, in order to highlight the contribution brought to the sustainable development.